The glass transition temperature investigation of polymers by molecular dynamic simulations - Saidakhmetov, P.; Piyanzina, I.; Baiman, G.; Nedopekin, O.; Tayurskii, D. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
In this paper, the process of glass transition is studied, the theory of which is not fully developed. Computer modeling can be used to understand the theory of this phenomenon. The glass transition temperature is influenced by a large number of polymer parameters: cooling rate, pressure, presence of diluent, structural features, etc. We are considering a number of different polymers to test the ability of the pcff+ force field to determine the glass transition temperature. The effect of tactility, composition, pressure and the presence of a diluent on the glass transition temperature of polymers will be shown using molecular dynamics (MD) and pcff+ force-field modeling. The effect of tact was studied using the use of atactic, isotactic and syndiotactic poly(methyl methacrylate) and atactic, isotactic and syndiotactic polypropylene. The LAMMPS code integrated into the MedeA computing environment was used to simulate the molecular dynamics of polymers. The calculation of the glass transition temperature at different cooling rates is closely related to the balanced initial systems. Due to the inability of current atomistic simulations to achieve the required cooling rates, as in experiments, the gap was not sharp and quite obvious. The data obtained show that the pcf+ force field describes tactics quite effectively and gives differences in the glass transition temperature for different types of tact. For polymers diluted with CO2, the glass transition temperature decreases almost linearly, which is in good agreement with the experiment. As expected, the pressure increases the glass transition temperature. However, at high pressure, the slope fracture disappears, and the determination of Tg becomes extremely difficult. The simulated annealing process will be applied to a set of polymers to obtain graphs of the specific volume versus temperature and determine the glass transition temperature.
Молекулалық-динамикалық модельдеу әдісімен полимерлердің шынылану температурасын зерттеу
Исследование температуры стеклования полимеров методом молекулярно-динамического моделирования
Keywords: cooling rate; pressure; glass transition temperature; pcff+; molecular dynamics simulations